Manajemen Pembelajaran Ramah Anak dalam Meningkatkan Kecerdasan Pada Anak Usia Dini - Mohammad Tijan Abrori (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
ABSTRACT The focus of this research is to analyze learning management in shaping children's intelligence at PAUD Mukhtar Syafa'at Blokagung. The type of research used is descriptive with a qualitative approach. The research subjects were teachers and school principals. To collect data, researchers used three techniques, namely: observation, interviews, and documentation. The way to check the validity of the data is by using triangulation. This research analyzes the data using Milles and Hubermant's theory, namely three interactive models starting from data reduction, data presentation and drawing conclusions. The result of this research is to find out how Mukhtar Syafa'at PAUD improves the intelligence of early childhood through learning management carried out by; Learning implementation planning is designed by mutual agreement within the school, taking into account the programs that have been established and things discovered later, the planning is also adjusted to the existing learning facilities and the abilities of the teaching staff in their respective fields. Learning is carried out in the classroom with more interesting media and various methods, which are child-centered. Evaluations are carried out to achieve quality learning for early childhood, by describing children's potential in the form of observations, work results, attendance lists and assignments.